Design of Quadrilateral Teaching Materials Assisted by GeoGebra in the Context of the Joglo Mosque UNESA 5 Campus - Sumarni Sumarni; Nafisyatul Azizah; Rahma Afinnisa Noviari; Ratu Mauladaniyati (Journal of Emerging Technologies in Ethnomathematics, 2026)
The integration of local culture and digital technology into mathematics learning has become an important strategy for creating meaningful learning experiences. However, learning materials about quadrilaterals are generally still abstract and rarely incorporate local cultural contexts supported by interactive technology. Therefore, this study aims to design learning materials for quadrilaterals by integrating the ethnomathematics context of the Joglo Al-Hasan Mosque at UNESA Campus 5, using the Realistic Mathematics Education (RME) approach, and GeoGebra as an interactive visualization tool. This study uses a Research and Development (R&D) approach that focuses on the design phase of the ADDIE model. The design process consists of needs analysis through a literature review, identification of quadrilateral concepts embedded in the mosque architecture, formulation of learning outcomes, preparation of learning activities, selection of learning methods and media, development of assessment instruments, and preparation of learning material designs. The resulting design integrates realistic learning scenarios, GeoGebra-assisted exploration activities, student worksheets, problem-solving tasks, and assessments aligned with the learning objectives. Learning activities are structured to facilitate students in building quadrilateral concepts through exploration, mathematical reasoning, discussion, and reflection based on meaningful real-life contexts. This study provides a theoretically grounded blueprint for developing culturally responsive and technology-enabled learning materials that support the implementation of contextual mathematics learning in the 21st century. Further research is recommended to continue the development, implementation, and evaluation stages to test the validity, practicality, and effectiveness of the proposed teaching materials.